2021
DOI: 10.1002/jcp.30601
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of electrogenic Na+/HCO3 cotransporter 1 (NBCe1) function and its dependence on m‐TOR mediated phosphorylation of Ser245

Abstract: Astrocytes are pivotal responders to alterations of extracellular pH, primarily by regulation of their principal acid-base transporter, the membrane-bound electrogenic Na + /bicarbonate cotransporter 1 (NBCe1). Here, we describe amammalian target of rapamycin (mTOR)-dependent and NBCe1-mediated astroglial response to extracellular acidosis. Using primary mouse cortical astrocytes, we investigated the effect of long-term extracellular metabolic acidosis on regulation of NBCe1 and elucidated the underlying molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(109 reference statements)
1
1
0
Order By: Relevance
“…First, NBCe1 protein abundance was determined by immunoblot analysis. Using an antibody raised against NBCe1, strong immunoreactive bands at ~110 kDa and ~130 kDa were detected in cell homogenates of all GBM cellular states, as previously described for mouse hippocampal and cortical astrocytes [ 14 , 15 , 16 ], ( Figure 1 A). These results were further confirmed by immunofluorescence, as shown in Figure 1 B,D.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…First, NBCe1 protein abundance was determined by immunoblot analysis. Using an antibody raised against NBCe1, strong immunoreactive bands at ~110 kDa and ~130 kDa were detected in cell homogenates of all GBM cellular states, as previously described for mouse hippocampal and cortical astrocytes [ 14 , 15 , 16 ], ( Figure 1 A). These results were further confirmed by immunofluorescence, as shown in Figure 1 B,D.…”
Section: Resultssupporting
confidence: 60%
“…We have previously shown that post-translational modifications of NBCe1, such as phosphorylation at distinct serine residues is a potent regulatory mechanism for NBCe1 transport capacity that is not accompanied by changes on protein levels [ 14 , 16 ]. Therefore, as a next step we investigated whether chemical hypoxia for 24 h may regulate NBCe1 transport activity, regardless of regulation of NBCe1 protein abundance, as is the case in MES-like in dependent GBM cells.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a substrate-mediated increase in transport activity, fast and efficient regulation of NBCe1 transport may occur via post-translational modifications such as phosphorylation or by changes in transporter trafficking to the plasma membrane, without changes in transcript or protein expression [29]. In the context of the present work, it is noteworthy that brain ischemia causes regulation of mTOR signaling (reviewed by [87]), which is known to be able to phosphorylate several residues of NBCe1, thereby altering its transport activity [88,89].…”
Section: Operation Of Nbce1 During Brief Chemical Ischemiamentioning
confidence: 88%